Influencing Factors of Mental Health Status of Dentists Under COVID-19 Epidemic - Li, Junping; Guo, Jiaoyang; Zhao, Juan; Guo, Yan; Chen, Cheng (Frontiers in Psychiatry, 2022)
Objective: To investigate dentists' psychological status and influencing factors in Shaanxi Province during the COVID-19 epidemic and assess their perceived wellness. Methods: The study was conducted among dentists from Shaanxi Province in China. The basic information was collected through the network questionnaire star platform. Depression, Anxiety, and Stress Scales (DASS-42) and Perceived Wellness Survey (PWS) were used to assess subjects’ psychological status and perceived wellness. Univariate linear regression analysis and multivariate analysis were performed on the influencing factors of depression, anxiety, and stress, and t-test and analysis of variance were used to analyze the perceived wellness results. Results: The results demonstrated that 33.2% of the surveyed dentists were in a state of depression, 37.1% were anxious, and 34.4% reported stress among 256 subjects. Linear Regression analysis results showed that: "years of working," "the impact of COVID-19 on their life, work, and sleep,” "worrying about occupational exposure/ virus infection," "lacking the awareness of prevention and control measures," "overtime work during the epidemic," "worrying about participating in the supporting work," and "continuous exhaustion from work" which were significant contributors to depression, anxiety, and stress status. In addition, the results of PWS found that each dimension of PWS was correlated with depression, anxiety, and stress state, which indicates the individual's physical and mental health state was associated with multiple factors. Conclusions: COVID-19 has significantly impacted dentists' mental health in Shaanxi Province. With these findings, we aim to educate and promote targeted interventions that can be utilized to improve dentists' mental health by analyzing the influencing factors.